The European Union and natural resources that fund armed conflicts: Explaining the EU's policy choice for supply chain due-diligence requirements. (September 2019) - Vlaskamp, Martijn C
Natural resources can be an important source of funding for warring parties in armed conflicts. Curbing the trade in these so-called conflict resources is, therefore, part of the European Union's conflict management policies. The article explores the EU's policies in this field and asks, specifically, why the EU is using supply chain due-diligence measures to achieve this goal. The author argues that they are the response to enforcement problems of most existing multilateral and unilateral sanction regimes because of state weakness in the targeted regions. This approach results from a broader idea from the EU that transparency can improve resource governance and, therefore, safeguard both its political and economic interests in conflict zones, such as the eastern Democratic Republic of the Congo. However, when the issue becomes specific—as in the EU Conflict Minerals Regulation—translating this idea into concrete policies becomes more contentious as the EU institutions set different priorities for the final policy design.